THE INTERACTION OF SOLUBLE HORSERADISH PEROXIDASE WITH MOUSE PERITONEAL MACROPHAGES IN VITRO - Steinman, Ralph M. (The Rockefeller University Press, 1972)
The in vitro interaction of soluble horseradish peroxidase (HRP) with homogeneous mono layers of mouse macrophages has been studied using sensitive biochemical and cytochemical techniques. The compartmentalization of HRP in extracellular and intracellular sites has been quantitatively evaluated. A significant fraction is bound to a serum-derived layer, which coats the surface of culture vessels and may be removed by appropriate washes. Macrophages interiorize HRP as a solute in pinocytic vesicles without appreciable binding of the glycoprotein to the plasma membrane. Uptake is directly proportional to the concentration of HRP in the culture medium. 1 x 10(6) cells ingest 0.0025% of the administered load per hr over a wide range of concentrations. Cytochemically, all demonstrable HRP is sequestered within the endocytic vesicles and secondary lysosomes of the vacuolar apparatus. After uptake, the enzymatic activity of HRP is inactivated exponentially with a half-life of 7–9 hr, until enzyme is no longer detectable. When macrophages have pinocytosed trace-labeled HRP-(125)I, cell-associated isotope disappears with a t ½ of 20–30 hr and they release monoiodotyrosine-(125)I into the culture medium. We were unable to obtain evidence that significant amounts of HRP (>2%) can be exocytosed after uptake, can exist intact on the cell surface, or can be digested extracellularly. It is difficult to reconcile these observations with several of the postulated mechanisms whereby macrophages are thought to play a prominent role in the induction of an immune response.